Pneumotoraks kod bolesnice sa pneumonijom izazvanom SARS-CoV-2 - Novković, Ljiljana; Čekerevac, Ivan (Vojnosanitetski pregled, 2021)
Introduction. The coronavirus disease 2019 (COVID-19) is an acute infectious multisystem disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), manifested by acute respiratory symptoms. The novel coronavirus pneumonia (NCP) is the most common serious clinical manifestation of SARS-CoV-2 infection. In the severe NCP, the systemic manifestations of the disease were also demonstrated, and one of the rare complications, first described in Wuhan (China), is pneumothorax. Case report. A 65-year-old female was admitted to the Clinic for Pulmonology with a high fever, shortness of breath, sore throat, and general weakness that started five days before. Laboratory findings revealed lymphopenia, elevated values ​​of inflammatory markers, and liver lesion. A chest X-ray (CXR) demonstrated diffusely accentuated interstitial pattern and reduced parenchymal transparency, left perihilar. Positive SARS-CoV-2 in a nasopharyngeal swab sample was detected in the real-time reverse transcription-polymerase chain reaction (RT-PCR), confirming the diagnosis of NCP. Immediately, nasal oxygen therapy with a flow rate of 8 L/min, with chloroquine phosphate, antibiotics, and symptomatic treatment, was initiated. On the 8th day, her condition suddenly deteriorated, and she developed severe hypoxemia. A repeated CXR showed complete left-sided pneumothorax. Thoracic drainage was successfully performed with complete reexpansion of the lungs the very next day. The patient was released from the hospital in good general condition with normal arterial blood gases. Conclusion. Pneumothorax may develop as a complication in patients with pneumonia caused by SARS-CoV-2, without previous pulmonary comorbidities, due to alveolar damage. Acute deterioration with rapid oxygen desaturation in these patients should raise the suspicion of pneumothorax. Early diagnosis and prompt treatment are necessary to reduce mortality.
Keywords: covid-19; pneumonia; pneumothorax; polymerase chain reaction; radiography